Key Construction Technology of HuSuTong Yangtze River Bridge. Issue 1 (2nd January 2023) - Gao, Zongyu; Xu, Wei; Mei, Xinyong; Zhang, Yanfei; Huo, Xuejin
Abstract: HuSuTong Yangtze River Bridge is a control project of the newly built HuTong Railway. The structure system is a cable-stayed bridge for highway and railway with a main span of 1092 m. The main girder is a steel truss structure with three main trusses. The upper deck of the highway is an orthotropic steel slab structure and the lower railway deck is a steel box structure. The upper and lower decks bear the force together with the main truss. The stay cables of the bridge are set as a three-cable plane structure. To meet the stress requirements, high strength bridge steel Q500qE and parallel wire stay-cables with a strength of 2000 MPa were developed. In terms of dynamic performance, the wind resistance of the structure is improved by using steel truss girders with good air permeability and setting the transverse wind resistance bearings at the pier towers. The damping and energy dissipation effect of the structure is remarkable by adopting a damping restraint system consisting of dampers and a friction pendulum bearings. In addition, through track geometry analysis and wind–vehicle–track–bridge coupling vibration analysis, a reference for running safety and comfort have been provided.